Overview of employment trends and projections. Issue 1 (5th August 2013) - Mourelo, Elva López; Khatiwada, Sameer; Corley‐Coulibaly, Marva
Abstract: This chapter presents an overview of the key labour market trends that have been shaping the world of work since the global economic crisis, from both global and regional perspectives. The chapter points to an uneven employment picture, with emerging and developing economies performing better than the majority of advanced economies. Furthermore, the chapter examines several structural dimensions of the current situation, notably long‐term joblessness, job quality and the social climate, as measured by the social unrest index.